PEl'lGEMBANGAN INTELLECTUAL CAPITAL DAN SOCIAL CAPITAL MELALUI PENDIDIKAN KEWARGANEGARAAN - Suyato Suyato (Jurnal Cakrawala Pendidikan, 2008)
Developingintellectu,,1 and social capital in preparing student for their future'srole as constructiveand critical citizen is essential in a healthy de~ocratic state,School-based civiceducation ,as one of means in building such ones faces somechallenges, Developing intellectual and capital, may be, is the greatest one. Thispaper tries to propose the urgency of such effort by arguing that school"based civiceducationCan be utilized as a means of making well informed citizen, The mainconcepts, such as democracy, citizenship, and responsibilities of governmentshould be understood by citizen properly and comprehensively. Therefore, theparamount challenge of civic education teachers is how to implement a teachingstrategy for best instilling those values, because people are not born with theknowledge, skills, and attitudes necessary to make democracy work; rather, theyacquire this knowledge and capacity for democratic citizenship .only Ihroughexperience,especially through 'School-based civic educa.tion, One of the beststrategies of civic education is portfolio-based teaching strategy. In this activity,studentshave an opportunity to practicing their values related to deIrtocracy,citizen,and responsibility of government. Besides its disadvantages, portfoliobased teaching strategy is a promising one in order to prepare the well informedcitizen veryneeded in a healthy democratic 'State. Accordingly, teachers of civiceducation should change their circumstances by implementing this strategy